1990
DOI: 10.1088/0953-4075/23/16/016
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of alignment of the L3subshell vacancy state produced after photoionisation in lead by 59.57 keV photons

Abstract: Experimental investigation of the alignment of the L, subshell vacancy state produced after photoionisation in lead by 59.57 keV photons has been reported. The present results confirm the prediction of the calculations of Flugge, Mehlhorn and Schmidt that the atomic inner-shell vacancies produced after photoionisation are aligned and the x-ray emission from the filling of vacancies in states with J P f is anisotropic, but contradict the predictions of Cooper and Zare that after photoionisation of the inner she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 19 publications
2
14
2
Order By: Relevance
“…Theoretical values of the alignment parameter for different states of various atoms calculated using the Herman-Skillman wave functions, have been reported by Berezhko and Kabachnik, (1977). The very strong anisotropy was reported for the emission of L lines for various elements by several scientists (Kahlon, et al, 1990a(Kahlon, et al, ,b, 1991aErtuğrul, et al, 1995Ertuğrul, et al, , 1996Ertuğrul, 1996Ertuğrul, , 2002Kumar, et al, 1999 Sharma andAllawadhi, 1999;Seven andKoçak, 2001,2002;Seven, 2004;Demir, et al, 2003). However, in all these investigations, the observed anisotropy is much higher than the predicted theoretical values of Scofield, (1976) and Berezhko and Kabachnik, (1977).…”
Section: Historical Background and Current Status Of Topicmentioning
confidence: 71%
See 1 more Smart Citation
“…Theoretical values of the alignment parameter for different states of various atoms calculated using the Herman-Skillman wave functions, have been reported by Berezhko and Kabachnik, (1977). The very strong anisotropy was reported for the emission of L lines for various elements by several scientists (Kahlon, et al, 1990a(Kahlon, et al, ,b, 1991aErtuğrul, et al, 1995Ertuğrul, et al, , 1996Ertuğrul, 1996Ertuğrul, , 2002Kumar, et al, 1999 Sharma andAllawadhi, 1999;Seven andKoçak, 2001,2002;Seven, 2004;Demir, et al, 2003). However, in all these investigations, the observed anisotropy is much higher than the predicted theoretical values of Scofield, (1976) and Berezhko and Kabachnik, (1977).…”
Section: Historical Background and Current Status Of Topicmentioning
confidence: 71%
“…The alignment parameter of the ions of Xe was obtained by Küst, et al, (2003). Kahlon et al, (1990a) reported experimental investigation of the alignment of the L 3 subshell vacancy state produced after photoionization in lead by 59.57 keV photons. The values of differential cross sections for the emission of the , , and X-ray lines were determined at different emission angles varying from 40 o to 120 o .…”
Section: Historical Background and Current Status Of Topicmentioning
confidence: 99%
“…Up to now, many experimental studies related with the angular distribution of the L 3 (J = 3/2) magnetic subshell X-ray transitions using different stimulating sources, such as synchrotron radiation [6][7][8], X-ray tube [9], radioisotope sources [10][11][12][13][14][15][16][17][18], and with charged particles [19][20][21][22][23][24] have been done.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have studied these phenomena using radioactive sources as the excitation beam, which are limited in energy tunability and photon flux delivered. The results reported are controversial, showing a wide range of values from very strong anisotropy [21][22][23][24][25][26][27] to a complete absence of that effect [28][29][30]. Synchrotron radiation was later used to determine the angular distribution of L lines of different elements taking advantage of this highly tunable and intense source of x-rays by two different groups [8,9].…”
Section: Introductionmentioning
confidence: 99%